CONTROl.. DE ERWINIA UREDOVORA CON MICROORGANISMOS ANTAGÓNICOS EN CUI..TIVOS DE PYRUS SP~ (PERO) (2013)
In order to dirninish the use of high doses of the chemical substances employed for the control of fire blight (Erwinia uredovora) in pear crops (Pyrus sp.), antagonistic microorganisms were isolated from the soil near healthy trees, from the rhizosphere, leaves, and stems of the sarne trees. To determine the antagonism in vitro, of these microorganisms against Erwinza uredovora, methods were used: channel, disk and strip. The best results were obtained with the disk method. The microorganisms which produced the largest inhibition halos were: Pseudomonasfluorescens biovar I (16 mm), Enterobacter agglomerans (15 mm) and Erwinia steawanii(14 mm).